2000
DOI: 10.1046/j.1523-1755.2000.00179.x
|View full text |Cite
|
Sign up to set email alerts
|

Importance of dialysis adequacy in mortality and morbidity of Chinese CAPD patients

Abstract: Our results show that dialysis adequacy has significant impact on outcome of Asian CAPD patients. Although we have excellent medium-term patient and technique survival, this favorable outcome should not prevent health care workers from providing adequate dialysis to Asian patients. The reason of discrepancy in outcome between Asian and Caucasian dialysis patients requires further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
191
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 190 publications
(223 citation statements)
references
References 22 publications
29
191
3
Order By: Relevance
“…However, even when the value was corrected with the formulae suggested by Joseph et al (26), serum albumin was still low in our subjects. Similar observation was made in our previous studies on peritoneal dialysis adequacy (13,27), but the cause of this discrepancy was not clear.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…However, even when the value was corrected with the formulae suggested by Joseph et al (26), serum albumin was still low in our subjects. Similar observation was made in our previous studies on peritoneal dialysis adequacy (13,27), but the cause of this discrepancy was not clear.…”
Section: Discussionsupporting
confidence: 72%
“…However, the effect of bicarbonate supplement in CAPD patients with Kt/V Ͻ2.1 has not been studied. It is important to note that although a weekly Kt/V of 2.1 was often regarded as the target of dialysis adequacy (12), we found that Chinese CAPD patients with a Kt/V of 1.7 had excellent outcome (13). The ADEMEX study further showed that increases in peritoneal Kt/V from 1.62 to 2.13 had no effect on patient survival (5).…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…The relationship between residual renal function and survival of prevalent PD patients, first reported by Maiorca et al (41), has now been repeatedly confirmed (42)(43)(44)(45)(46). These findings were further corroborated by the re-analysis of the Canada-USA (CANUSA) study wherein each 5-L/wk per 1.73 m 2 higher mean of urea and creatinine clearances was associated with a 12% decrease in the relative risk for death (47).…”
Section: Possible Biologic Explanations For Differences In Outcomes Bmentioning
confidence: 79%
“…Additionally, we assessed the prognostic values of LBM in all-cause mortality risk in a large retrospective PD cohort study because LBM should be a significant predictor of outcome events in PD patients (3,(8)(9)(10).…”
mentioning
confidence: 99%